HUBUNGAN KEANEKARAGAMAN KONSUMSI PANGAN DAN AKTIFITAS FISIK DENGAN KEGEMUKAN REMAJA DI SMPN KAMPAR KIRI KABUPATEN KAMPAR - MARINI ARIESTA; MITRA MITRA; SRI DESFITA; NURLISIS NURLISIS; HERYUDARINI HARAHAP (Universitas Pahlawan Tuanku Tambusai, 2021)
AbstractThe 2013 World Health Organization (WHO) defines obesity as an abnormal accumulation of body fat which can cause health risks. The aim of the study was to find out the relationship between diversity of food consumption and physical activity with adolescent obesity The type of research used was analytical cross-sectional, the research locations were SMPN 2, SMPN 3 and SMPN 4 Kampar Kiri. The study population was 267 students. The number of samples is 165 students. The method of collecting data on diversity of food consumption using the dietary diversity score index, physical activity using physical activity quesionaire for adolescent, height was measured using microtois weight weighed using digital scales. Data analysis was done by multivariate multiple logistic regression. The results of research on physical activity were 3 times at risk for obesity (95% CI = 1,519-6,365), pocket money 4 times at risk of obesity (95% CI = 1,947-9,015), fast food 2 times at risk of obesity (95% CI = 1,186â€“ 4.720). Conclusions obtained three significant variables with adolescent obesity, physical activity, pocket money and fast food. Confounding variable diversity of food consumption. Suggestion: Increasing physical activity with extracurricular activities three times a week for 30 minutes as recommended by the healthy community movement, given diverse, nutritious and balanced food counseling according to the contents of my plate so that nutrients are consumed in sufficient quantities and not excessive.Keywords:Â physical activity; obesity; fast food; pocket money